Genetic Reduction in Left Ventricular Protein Kinase C-α and Adverse Ventricular Remodeling in Human Subjects. (March 2018) - Hu, Ray; Morley, Michael P.; Brandimarto, Jeffrey; Tucker, Nathan R.; Parsons, Victoria A.; Zhao, Sihai D.; Meder, Benjamin; Katus, Hugo A.; Rühle, Frank; Stoll, Monika; Villard, Eric; Cambien, François; et al.
Abstract : Background: Inhibition of PKC-α (protein kinase C-α) enhances contractility and cardioprotection in animal models, but effects in humans are unknown. Genotypes at rs9912468 strongly associate with PRKCA expression in the left ventricle, enabling genetic approaches to measure effects of reduced PKC-α in human populations. Methods and Results: We analyzed the cis expression quantitative trait locus for PRKCA marked by rs9912468 using 313 left ventricular specimens from European Ancestry patients. The forward strand minor allele (G) at rs9912468 is associated with reduced PKC-α transcript abundance (1.7-fold reduction in minor allele homozygotes, P =1×10 −41 ). This association was cardiac specific in expression quantitative trait locus data sets that span 16 human tissues. Cardiac epigenomic data revealed a predicted enhancer in complete ( R 2 =1.0) linkage disequilibrium with rs9912468 within intron 2 of PRKCA. We cloned this region and used reporter constructs to verify cardiac-specific enhancer activity in vitro in cardiac and noncardiac cells and in vivo in zebrafish. The PRKCA enhancer contains 2 common genetic variants and 4 haplotypes; the haplotype correlated with the rs9912468 PKC-α–lowering allele (G) showed lowest activity. In contrast to previous reports in animal models, the PKC-α–lowering allele is associated with adverse left ventricular remodeling (higher mass, larger diastolic dimension), reduced fractional shortening, and higher risk of dilated cardiomyopathy in human populations. Conclusions: These findings support PKC-α as a regulator of the human heart but suggest that PKC-α inhibition may adversely affect the left ventricle depending on timing and duration. Pharmacological studies in human subjects are required to discern potential benefits and harms of PKC-α inhibitors as an approach to treat heart disease. Abstract : Supplemental Digital Content is available in the text.